ESTEVES & ESTEVES, UMA POÉTICA DOS TEXTOS EM MOVIMENTO: INTERTEXTUALIDADE ENTRE A MÁQUINA DE FAZER ESPANHÓIS E TABACARIA - Tomé, Rodrigo da Silva (2017)
This paper aims to analyze the Portuguese novel a máquina de fazer espanhóis from the intertextual relation with the poem Tabacaria. More specifically, the analysis are be made by means of the character Esteves and its textual intertwining that we recognize between the two works. The corpus of this study has its bases in scanning that name/character that appears in both the novel and the poem in order to observe similarities and differences on the composition of this subject who is said to be ‘without metaphysics’. About the analysis, more than just describe the parts in which Esteves appears and compare them to the poem, it is necessary to infer about the signification of that name/character that disturbs the narratives by keeping them in constant movement and open to re/interpretations. Esteves thus becomes synonymous with the literary in-between place in the romance. The theoretical premise of this paper will be Samoyault (2008). In her book Intertextualidade, the French author proposes to think the literature memory as a poetics of the moving texts. Therefore, the analysis will use a non-formalist and non-typological approach,but aimed to the study of the numerous relations that rise from the contact between the texts themselves.